Pengenalan Higiene dan Sanitasi dalam Pengolahan Kopra Pada Home Industry Kopra Desa Muara Telang Kabupaten Banyuasin - Handayani, Marta Tika Handayani; Riani, Ira Gusti; Khairunnisa, Eka Nurriza (Adi Widya : Jurnal Pengabdian Masyarakat, 2023)
Muara Telang village is one of the villages in Banyuasin district which produces coconuts. There are many copra processing home industries in the area. One of the copra processing home industries is A'A Yusma's home industry. Copra is processed manually and without regard to higiene and sanitation aspects in copra processing. This is the background for the introduction of higiene and sanitation in copra processing in the copra home industry. The activity was carried out on January 15 2023 offline in the form of training/counseling and was attended by 15-20 people. The activity went smoothly and the community enthusiastically participated in this activity. It is hoped that this activity will raise awareness of the importance of higiene and sanitation in copra processing and apply higiene and sanitation in copra processing. Keywords: Introduced, Higiene and sanitation, Copra’s industry, Banyuasin.